2017
DOI: 10.1021/acs.macromol.7b01107
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Mechanism and Cross-Link Structure of Nadic End-Capped Polymers: A Quantum Mechanical and Microkinetic Investigation

Abstract: The applications of norbornene or nadic end-capped high performance polymers (HPPs) are manifold and have been discussed in the literature for more than two decades. The cross-links formed from nadic end-cap determine the mechanical and thermal properties of these polymers. In spite of extensive studies, the cross-link structure and the cross-linking mechanism of nadic end-capped polymers remain elusive. Quantum chemical computations together with microkinetic modeling are used here to elucidate these aspects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The polymerization behaviors of benzoxazine resins, , norbornene-containing polymers, , and phthalonitrile polymers have been extensively investigated, respectively. However, the thermally activated polymerization and the structural transformation of a benzoxazine monomer containing both norbornene and phthalonitrile functionalities have never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerization behaviors of benzoxazine resins, , norbornene-containing polymers, , and phthalonitrile polymers have been extensively investigated, respectively. However, the thermally activated polymerization and the structural transformation of a benzoxazine monomer containing both norbornene and phthalonitrile functionalities have never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It can be explained for the complex effect of thermal oxidation or degradation and instability characteristic of NA. [7] On the other hand, there was a remarkably unusual phenomenon that PA-PI-C film showed relatively smaller transmittance and larger b value than PA-PI-T film. The chemical imidization method did not show any advantage for the optical transparency of PA end-capped PI films before or after reheating treatment.…”
Section: Effects Of Chemical Structures Of End-capping Reagents and Imidization Methods On Optical Propertiesmentioning
confidence: 99%
“…Then, there are some inherent defects in the obtained polyimides usually, such as high porosity and poor performance stability, which limit the applications of polyimides in high‐precision devices and large size processing 13 . The approach of synthesizing end‐capped amide‐acid pre‐polymers was introduced by Lubowitz 3 and Burns et al 4 and has been reported massively as an effective route to improve processability 14–18 . As a notable example, PMR‐15, developed by NASA Research Center through in situ polymerization of monomer reactants (PMR) in 1970s, is a milestone achievement 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from its low melt viscosity and better processing window, PMR‐15 composites have been widely used in airplanes, automobiles, and off‐shore oil‐drilling platforms 3,19 . However, the poor thermo‐oxidative and storage stability, harsh curing conditions (600 K, 200–500 psi) as well as the brittleness of cured PIs limited the applications of norbornene (NE) end‐capped prepolymers 14,20 . Due to forming aromatic cross‐linking structure introduced phenylethynyl terminated imide, the thermo‐oxidative stability and toughness of PIs were effectively improved.…”
Section: Introductionmentioning
confidence: 99%